The Effect of FourWeeks of Beta-Alanine Supplementationon Anaerobic Power and Plasma Lactate Level in Unprofessional Male Bodybuilders - Mahdi Rezagholizadeh (Türk Spor ve Egzersiz Dergisi)
The aim of current study was to investigate the effect of four weeks of beta-alanine supplementation on anaerobic power and plasma lactate level of unprofessional male bodybuilders. For this purpose, the study plan was performed as pretest-posttest with control group and as one blind trial. 20 mature and unprofessional athletes were randomly divided into two groups of 10 people including supplement and placebo (supplement group: 25±0.81 years old, weight 82.10kg±4.78 kg and BMI 24.34±2.19kg/m2 and placebo group: 24.40± 1.07 years old, weight 80.60±5.85 kg and BMI 23.34±1.16 kg/m2). Within experimental period of four weeks, the subjects of supplement group received six mg daily beta-alanine supplement for five days a weeks and the subjects of placebo group received placebo to the same dosage (Aspartate Flavor Powder). Both groups also participated in four weeks of bodybuilding exercises, designed by the researcher. As pretest and posttest, the subjects of both groups participated in anaerobic test of RAST respectively in one day before and after finishing experimental period to evaluate the indicators of anaerobic power and to measure blood lactate levels. Blood samples were taken from them immediately after RAST test. To analyze data, dependent t-test as well as two-way covariance analysis test was used. Statistical operations were checked in significance level of P≤0.05 and then the following results were obtained: compared to placebo group, four weeks of beta-alanine supplementation led to significant improvement of anaerobic peak power and fatigue index of subjects (P≤0.05) but it didn’t have any significant effect on average anaerobic power and plasma lactate level following one session of intense anaerobic activity. Since, increased anaerobic peak power and reduced fatigue can indicate improvement of subjects’ anaerobic power, it can be concluded that this type of supplementation has caused improvement of participants’ anaerobic power.